2012
DOI: 10.3109/07435800.2011.639319
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Kisspeptin Levels in Pregnancies with Diabetes and Hypertensive Disease as a Potential Marker of Placental Dysfunction and Adverse Perinatal Outcome

Abstract: Our study demonstrates reduced kisspeptin levels in pregnancies with diabetes, H, PE, and placental dysfunction. In patients with PE and placental dysfunction, decreased kisspeptin levels were associated with adverse perinatal outcome. Larger studies are needed to investigate the role of kisspeptin as a potential marker of placental dysfunction and adverse perinatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 28 publications
1
53
1
1
Order By: Relevance
“…Therefore, the higher circulating kisspeptin levels during normal pregnancy may play a physiological role to enhance insulin secretion to protect the mother and foetus from increasing glucose levels and the development of gestational diabetes mellitus. In keeping with this hypothesis, pregnant women with diabetes have lower kisspeptin levels than pregnant women without diabetes 47. In addition, previous rodent work has shown that selective ablation of the kisspeptin receptor, kiss1r , from pancreatic islet β‐cells in pregnant mice results in impaired glucose tolerance and reduced insulin secretion 48.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, the higher circulating kisspeptin levels during normal pregnancy may play a physiological role to enhance insulin secretion to protect the mother and foetus from increasing glucose levels and the development of gestational diabetes mellitus. In keeping with this hypothesis, pregnant women with diabetes have lower kisspeptin levels than pregnant women without diabetes 47. In addition, previous rodent work has shown that selective ablation of the kisspeptin receptor, kiss1r , from pancreatic islet β‐cells in pregnant mice results in impaired glucose tolerance and reduced insulin secretion 48.…”
Section: Discussionmentioning
confidence: 74%
“…15 On the other hand, it has been shown that ablation of dynorphin causes increase of fatty acid oxidation in male mice, reduction in adiposity, and increased weight loss during fasting, probably due to decreases in intestinal nutrient absorption. 16 There has been no study performed about neurokinin B in relation with insulin resistance, or glucose intolerance, and dynorphin does not seem to essentially affect glucose homeostasis.…”
Section: Onset Of Adolescence Tanner Staging and Glucose Metabolismmentioning
confidence: 99%
“…However, the authors suggested that both series of results reflect the determining role that kisspeptin plays in moderating implantation in the first trimester. Other studies have replicated these findings, with Armstrong and coworkers finding lower circulating kisspeptin values at 16-20 weeks' gestation in patients who subsequently developed pre-eclampsia and intrauterine growth restriction (Armstrong et al 2009) and Cetovic and coworkers demonstrating significantly lower circulating kisspeptin in pregnancies affected by type 1 diabetes, pre-eclampsia, gestational hypertension and gestational diabetes (Cetovic et al 2012).…”
Section: Implantation and Placental Functionmentioning
confidence: 82%